Validation of an analytical method by high-performance liquid chromatography and microbiological assay, biological safety and in silico toxicity for danofloxacin (Brazilian Journal of Pharmaceutical Sciences, 2020)
Danofloxacin is a veterinary fluoroquinolone used to treat respiratory and gastrointestinal diseases of birds, pigs and cattle. The literature reviewed shows some analytical methods to quantify this fluoroquinolone, but microbiological and biological safety studies are limited. The analytical methods were validated by the Official Codes. The LC-DAD method was developed and validated using an RP-18 column, mobile phase containing a mixture of 0.3% triethylamine (pH 3.0) and acetonitrile (85:15, v/v). The microbiological assay was performed by agar diffusion method (3 x 3) and Staphylococcus epidermidis as a microorganism test. Forced degradation studies were performed in both methods. The minimum inhibitory concentration (MIC) was performed by test microdilution and toxicity studies were evaluated using in silico study, cell proliferation, cell viability test, micronuclei and comet assay. LC and a microbiological assay proved linear, accurate, precise, and robust to quantify danofloxacin, but only the LC method showed selectivity to quantify the drug in the presence of its degradation products. These results demonstrate that the LC method is suitable for stability studies of danofloxacin, but a microbiological assay cannot be used to quantify the drug due to the biological activity of the photoproducts. Ex-vivo cytotoxicity and theoretical and experimental genotoxicity were also observed.